The KCNE Tango – How KCNE1 Interacts with Kv7.1 - Wrobel, Eva; Tapken, Daniel; Seebohm, Guiscard (Frontiers in Pharmacology, 2012)
The classical tango is a dance characterized by a 2/4 or 4/4 rhythm in which the partners dance in a coordinated way, allowing dynamic contact. There is a surprising similarity between the tango and how KCNE β-subunits “dance” to the fast rhythm of the cell with their partners from the Kv channel family. The five KCNE β-subunits interact with several members of the Kv channels, thereby modifying channel gating via the interaction of their single transmembrane-spanning segment, the extracellular amino terminus, and/or the intracellular carboxy terminus with the Kv α-subunit. Best studied is the molecular basis of interactions between KCNE1 and Kv7.1, which, together, supposedly form the native cardiac IKs-channel. Here we review the current knowledge about functional and molecular interactions of KCNE1 with Kv7.1 and try to summarize and interpret the tango of the KCNEs.